Analisis Perencanaan Anggaran Dalam Pengelolaan Keuangan Desa: (Studi Kasus Pada Desa Candiretno) - Septynia Heryudini; Defa Oktaviani; Cicih Widianingsih; Anisa Muktidena Mutiara Astri; Eva Wulandari (International Forum of Researchers and Lecturers, 2024)
This research aims to analyze the flow/process of village financial management planning and analyze how villages can design the preparation of the Village Revenue and Expenditure Budget (APBD) in Candiretno Village, Secang District, Magelang Regency. The results of village development planning deliberations (MUSRENBANGDES) are used as the basis for preparing the Village Government Work Plan (RKPDesa) which serves as a guideline for the use of village funds in accordance with development priorities and community aspirations. The aim of preparing village government work plans is to improve the welfare of village communities and improve the quality of life of village communities. The village development index through customer satisfaction questionnaires is used to evaluate the success of villages in achieving inclusive and sustainable development.